Life from the bright side: Sociology and the imagining of the radically different (Sociologisk Forskning, 2023)
The purpose of this article is to investigate how sociological imagination can be put to work for creating notions of the radically different as an alternative to the contemporary strategy of green growth for understanding and managing the climate crisis. Based on current growth critical research literature, it examines how a number of authors have envisioned a future society characterized by degrowth. The analytical approach of the article is to try to discern patterns and tendencies through a systematic review of scientifically based future images. Such an approach can be said to be in line with the broader program that seeks to demonstrate the importance of sociology for societal change and, by extension, how we imagine and reconstitute the world beyond the climate crisis. Examples of what life in a future degrowth society could look like are presented based on its impact in four overall areas: lifestyle, infrastructure, governance and organization, and work and economy. Imaginings of the radically different are further illuminated through some prominent sociologists´ reasoning about the concept of utopia.